Every drop counts: Assessing aid for water and sanitation - P.B. Anand (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
Water and sanitation sectors have been the 'natural' subjects of aid for several decades. However, these sectors also were among those most affected by changes in aid approaches and tools. The aim of this paper is to capture some of the complexity in assessing impact and effectiveness of aid in water and sanitation sector. Notwithstanding this complexity, the paper aims to explore some of the key factors that influence successful and effective use of aid. Though the overall magnitude of aid to water supply and sanitation activities has increased significantly, it is not easy to connect aid with specific outcomes such as reduction on mortality due to waterborne diseases or number of people with improved access. Though water supply and sanitation sector attracts about 7.4 billion dollars of aid this is perhaps smaller than what is needed to achieve the Millennium Development Goal sanitation target let alone fully realizing the human right to water and sanitation. The paper discusses some key challenges in making aid in water supply and sanitation more effective. Donors need to be aware of the 'accountability paradox' by which a demand for greater accountability can push investments away from much needed but difficult to measure institutional reforms towards easily measurable but perhaps somewhat less effective physical infrastructure. As the 'low hanging fruit' have been taken, making further progress may require the development of appropriate tools so that aid is used more often in effectively catalysing a range of institutions in finding solutions and less in terms of directly investing in delivery of services.
Keywords: H87; N50; O18; Q53; Q25; 330; water supply; sanitation; health; aid; effectiveness